Single nucleotide polymorphism rs7908486 of the TCF7L2 gene is highly associated with obesity in the Iraqi population - Mohammed Amera K.; Al-Thuwaini Tahreer M.; Al-Shuhaib Mohammed Baqur S. (Archives of Biological Sciences, 2021)
This study was conducted to assess the possible association between polymorphisms of the transcription factor 7-like 2 (TCF7L2) gene and obese Iraqi adults. DNA was obtained from 158 obese subjects and 142 controls. Two specific PCR fragments were designed to incorporate two highly frequent single nucleotide polymorphism (SNP)s within TCF7L2, rs11196208 and rs7908486. Both amplified loci were genotyped by PCR-single-strand conformation polymorphism (SSCP) followed by sequencing. Logistic regression analysis was performed to detect the association between both genetic variants and obesity. Concerning rs11196208-based amplicons, PCR-SSCP genotyping showed homogeneous banding patterns for all investigated samples. In contrast with rs11196208, three SSCP banding patterns in the rs7908486-based amplicons, GG, AG and AA, were observed. Individuals with the AA genotype showed significantly higher (P<0.05) body mass index (BMI), waist circumference (WC), fasting blood glucose (FBG), and insulin values than those with either AG or GG genotypes. Association analysis revealed that individuals with the A allele exhibited a greater risk of obesity than individuals with the B allele. Data indicate that rs7908486 SNP exerted a tight association with obesity. The study suggests implementing TCF7L2 rs7908486-based genotyping in the early detection of obesity.